ARTRÓPODES BENÉFICOS ASSOCIADOS AO ESTERCO DE GALINHAS POEDEIRAS NO BRASIL - Berti Filho, Evoneo; Thomazini, Marcílio José; Costa, Valmir Antonio (REVISTA DE AGRICULTURA, 2015)
ARTRÓPODES BENÉFICOS ASSOCIADOS AO ESTERCO DE GALINHAS POEDEIRAS NO BRASIL